The level of effect of tightening of steel reinforcing a 16mm gauge when the reinforced concrete is exposed to fire with varying concrete cover distance: مدى تأثر قوى الشد لحديد تسليح قياس 16مم عند تعرض الخرسانة المسلحه به للنار مع أختلاف مسافة الغطاء الخرساني - M. Dawood Salem Jasim Al - Kandari (Journal of engineering sciences and information technology, 2017)
This research is to study how the fire affecting the tensile strength of two samples for reinforced concrete with different dimension of concrete covered the steel bar diameter was 16 mm. a two form made from wood and the 16mm steel bar embedded inside when the concrete poured then the form was opened after 7 days then the sample has been exposed to fire for 80 minutes then after it cooled up the steel bar had been taken to tensile test.